Determinants of Informal Sector Workers' Income in Mataram City - M. Syahrul Azim; Luluk Fadliyanti; Vici Handalusia Husni (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
The informal sector is important for people whose economic level is less. So this informal sector can be used as a job and source of income and maximise profits by working on activities in the informal sector. This study aims to analyse the determinants of income of informal sector workers in Mataram City, West Nusa Tenggara. This study uses multiple linear regression method and quantitative approach to examine the impact of variables such as education level, training, gender, and working time on the income of informal sector workers in Mataram City. A sample of 180 people was selected through purposive sampling, with the main data coming from Statistics Indonesia and the 2022 National Labour Force Survey. The results show that training individually has a negative and significant impact on the income of informal sector workers in Mataram City, while working time has a positive and significant impact. However, education and gender have no significant impact individually. Overall, the variables of education, training, gender, and working time simultaneously have a positive and significant impact on the income of informal sector workers in Mataram City.